Challenges of Location-Based Services market analysis: current market description - Basiri, Anahid; Moore, Terry; Hill, Chris; Bhatia, Paul (Springer International Publishing, 2015)
Location-Based Services (LBS) have a huge and rapidly growing market, however LBS market reports do not fully agree about the current market size, the exact number of LBS users, market growth rate, etc. Different market study reports describe LBS market size, number of LBS subscribers and frequent users, revenues and costs and most appreciated application types with different and sometimes extremely contrasting numbers and figures and this becomes more problematic when it comes to forecasting the future market of LBS. One of the very first steps in any market analysis is defining business contribution area, which decides what should be included in or excluded from the market analysis. Location based services has got a large market; therefore it is not an easy task to identify LBS market’s boundaries to analyse what is inside the box as LBS applications and exclude the rest. This paper explains the impact of such vague boundaries on market size estimation.